PEUSIJUEK AS TRADITION: CULTURAL CONSTRUCTION AND ITS MEANING FOR THE PEOPLE OF ACEH SELATAN - Anida, Anida; Ristawati, Ristawati (JURNAL AL-IJTIMAIYYAH, 2024)
The Peusijuek tradition in Aceh Selatan represents a cultural construction that integrates Islamic values with Hindu cultural heritage. The historical process of Peusijuek is rooted in the peaceful Islamization that occurred since the 7th century AD, allowing local practices to assimilate with Islamic teachings. This research is a field study aimed at examining how the construction of the Peusijuek tradition is manifested in Aceh Selatan society. The findings indicate that although Hindu elements initially influenced this tradition, Peusijuek has transformed into a ritual that emphasizes prayers for safety and Islamic teachings. The implementation of Peusijuek is led by community leaders or village imams, with each element, from materials to movements, possessing profound symbolism that embodies harmony and fertility. This construction of tradition reflects the adaptation and transformation of cultural heritage within a religious context, maintaining the relevance of Peusijuek in the modern era through integration into various events. As a medium for imparting noble values, Peusijuek plays a crucial role in strengthening the cultural identity of the Aceh Selatan community, creating a bridge between the current generation and the past.